PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN GURU PPKN TERHADAP KESESUAIAN PROSES PEMBELAJARAN PADA MATA PELAJARAN PPKN - Lina Marlina (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2022)
ABSTRACT This study aims to determine the extent of the suitability of a teacher in compiling a learning implementation plan on Civics subjects at SMA Maulana Yusuf Kota Serang with the learning process carried out by the teacher during the teaching process in the classroom so that the flow of the learning implementation plan prepared by the teacher can be said. appropriate and serve as teaching guidelines and by the stages of learning steps from the introduction, core, and closing. In this study, the researcher used a qualitative descriptive method because in this study, the title Preparation of the PPKn Teacher Learning Implementation Plan on the Suitability of the Learning Process in Civics Subjects, was by this research method, the data obtained were processed by descriptive analysis. And the results of this study it can be said that the preparation of the PPKn Teacher Learning Implementation Plan on the Suitability of the Learning Process in Civics Subjects at Maulana Yusuf High School it can be said to have been by the learning process carried out by Civics Education teachers at Maulana Yusuf High School Serang City with the support from the head schools, namely by supervising teachers of Civics subjects during the learning process in the classroom.